Semi-transparent perovskite solar cells with bidirectional transparent electrodes. (April 2021) - Lim, Sang-Hwi; Seok, Hae-Jun; Kwak, Min-Jun; Choi, Dong-Hyeok; Kim, Su-Kyung; Kim, Do-Hyung; Kim, Han-Ki
Abstract: In this study, we report on high performance semi-transparent perovskite solar cells (PSCs) with bidirectional transparent electrodes for use in building-integrated photovoltaics (BIPV). Using a typical magnetron sputtered InSnO (ITO) anode and a low energy sputtered InZnSnO (IZTO) cathode, we fabricated bidirectional transparent electrodes for semi-transparent PSCs. In particular, by the sequential sputtering of a thin buffer and then a thick dense IZTO layer (two-step sputtering), we fabricated a transparent IZTO cathode for a p-i-n planar type PSC without any plasma damage. Compared to the power conversion efficiency (PCE 3.43%) of PSCs with an ITO cathode prepared by typical DC magnetron sputtering, the PSC with a two-step sputtered IZTO cathode showed a much higher PCE (15.72%) due to the absence of plasma damage. The high PCE of the semi-transparent PSC with IZTO cathode is comparable to the PCE (17.04%) of an opaque PSC with opaque Ag cathode. Furthermore, with diluted perovskite solution, we able to achieve PCE of 13.61% and AVT of 24.70% both high enough to use as PSC for BIPV. These results demonstrate that the two-step linear facing target sputtering (FTS) process is a feasible approach to make high-quality transparent top cathodes for semi-transparent PSCs. Considering the mass-production of semi-transparent PSCs for BIPV, FTS-based two-step sputtering has great potential to become a key technique for producing smart windows that will replace typical solution coating or other complicated transfer processes. Graphical Abstract: ga1 Highlights: Semi-transparent perovskite solar cells with bidirectional transparent electrodes were successfully fabricated. A two-step linear FTS process for PSC that causes no plasma damage was demonstrated. A high PCE (15.72%) was achieved for semi-transparent PSC with a TS-IZTO cathode. The plasma damage free sputtering mechanism of our linear FTS process was thoroughly investigated and elucidated.